COMPARISON OF OPTIMAL PORTFOLIO PERFORMANCE BETWEEN SINGLE INDEX MODELS AND MARKOWITZ MODELS (CASE STUDY OF DAILY RETURN IMPLEMENTATION OF OJK RULES REGARDING INVESTMENTS OF STATE VALUES FOR NON-BANK FINANCIAL INSTITUTIONS 2016-2017) - Kaolina Savitri Setyantho; Sasmito Hadi Wibowo (Business and Entrepreneurial Review, 2019)
The problem of this research is the implementation of optimal portfolio of Government Security investment by Non-Bank Financial institutions. Otoritas Jasa Keuangan (OJK) provides rules for it. This study utilizes several financial indexes to find the optimal portfolio. Some portfolios are developed and tested by comparing risk levels through single index model and Markowitz Models. Furthermore, the returns of standard deviation and coefficient of variance are used to identify this optimal model. The result shows that developing optimal portfolio through Single Index Model yields higher expected return than that of Markowitz Model. Choosing Kompas 100 Index as the reference index may help higher expected return. Due to the nature of the Indonesia Health Care Agency, is suggested that agency is excluded from the Financial Service Authority rules regarding obligation and stock investment. The limitation of this research is as follows: it focuses on two approaches, analyses on investment obligations and stocks, and the healthcare agency only.